2019
DOI: 10.4236/cm.2019.104007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Investigation of “Meridian Tropism” in Three “Shen” Chinese Herbs

Abstract: "Meridian tropism" refers to the organ-specific biological action(s) produced by a Chinese herb following its oral administration, which is analogous to the concept of "bioavailability" in Western medicine. In this study, we compared the in vitro and ex vivo pharmacological actions of three herbs [namely, Dangshen (DS, Codonopsis Radix), Ranshen (RS, Ginseng Radix) and Xiyangshen (XYS, Panacis Qinquifolii Ra-dix)] to validate their meridian tropism. We compared the in vitro and ex vivo pharmacological actions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…7 Panax ginseng can preferentially act on the "Heart" "Spleen" and "Lung" based on the "meridian tropism" theory. 11 Studies have shown that Panax ginseng can increase the primary spleen cell proliferation and boost the ATP production in the colonic epithelial cells of Caco-2 cultured in vitro, 12 which is consistent with the TCM theory that the Spleen meridian includes both the spleen and the intestinal system. 11 Other study also demonstrated significant increases in ATP in H9c2 cardiomyocytes in vitro when supplemented with Panax ginseng.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…7 Panax ginseng can preferentially act on the "Heart" "Spleen" and "Lung" based on the "meridian tropism" theory. 11 Studies have shown that Panax ginseng can increase the primary spleen cell proliferation and boost the ATP production in the colonic epithelial cells of Caco-2 cultured in vitro, 12 which is consistent with the TCM theory that the Spleen meridian includes both the spleen and the intestinal system. 11 Other study also demonstrated significant increases in ATP in H9c2 cardiomyocytes in vitro when supplemented with Panax ginseng.…”
Section: Discussionsupporting
confidence: 53%
“…11 Previous studies found that ethanolic extract of Panax ginseng significantly enhanced the growth of primary spleen cells in the spleen, and boosted ATP production of Caco-2 colonic epithelial cells in vitro which is consistent with the TCM meridian theory that the Spleen meridian includes the function of both the spleen and the intestinal system. 12 The hypothesis of this study is that Qi-invigorating herbs 1) boost ATP production in mitochondria and 2) increase the antioxidant capacity simultaneously for specific organs of animals based on the meridians it belongs to. To examine this hypothesis, we conducted animal experiments to study the effect of Panax ginseng extracts on various tissues including heart, hiver, spleen, sung, kidney, brain and skeletal muscle tissues, and compared the energy metabolism and antioxidant changes of mitochondria in lung, spleen and heart tissues with those in other tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consist with this, a previous study using both in-vitro and in-vivo studies with animals, has shown that Panax Ginseng, a famous "Qi-invigoration" herb, is capable of enhancing mitochondrial energy production in both the H9c2 cardiomyocytes and rat hearts [22]. Furthermore, a recent experimental study showed that "Qi-invigoration" by Panax Ginseng stimulated the proliferation of cultured rat splenocytes and increased mitochondrial energy levels in rat intestine [23].…”
Section: Discussionmentioning
confidence: 82%